1988
DOI: 10.1007/bf01128019
|View full text |Cite
|
Sign up to set email alerts
|

Expression, isolation and properties of Fur (ferric uptake regulation) protein ofEscherichia coli K 12

Abstract: The cloned fur (ferric uptake regulation) gene of Escherichia coli K12 was ligated to an expression vector which was inducible with nalidixic acid. The Fur protein was isolated in a single step by immobilized metal-ion-affinity chromatography over zinc iminodiacetate agarose. The amino acid composition of the isolated protein agreed with that predicted from the gene sequence and indicated post-transcriptional removal of the N-terminal methionine residue. All four cysteines were shown to be present as thiols. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 22 publications
10
82
0
Order By: Relevance
“…The probe's migration through a polyacrylamide gel was retarded after adding increasing concentrations of Fur (figure 4A), indicating that Fur bound the iha promoter region. Multiple shift products were observed, as has been described for Fur [25,26]. Abundance of the higher molecular weight complex was decreased when the binding reaction was incubated in increasing (competitive) concentrations of unlabeled probe or of a short double-stranded oligonucleotide consisting of only the putative iha Fur-binding site flanked by 7 bp on either side ( figure 4C).…”
Section: Interaction Of the Iha Promoter With Furmentioning
confidence: 86%
See 1 more Smart Citation
“…The probe's migration through a polyacrylamide gel was retarded after adding increasing concentrations of Fur (figure 4A), indicating that Fur bound the iha promoter region. Multiple shift products were observed, as has been described for Fur [25,26]. Abundance of the higher molecular weight complex was decreased when the binding reaction was incubated in increasing (competitive) concentrations of unlabeled probe or of a short double-stranded oligonucleotide consisting of only the putative iha Fur-binding site flanked by 7 bp on either side ( figure 4C).…”
Section: Interaction Of the Iha Promoter With Furmentioning
confidence: 86%
“…pET21dFur was transformed into BL21(DE3) (Novagen), and the purification strategy was based on previously published methods [48,25,26]. An overnight culture was diluted 1:100 and grown to OD 600 = 0.6 while shaking at 37°C.…”
Section: Fur Purificationmentioning
confidence: 99%
“…This value is relatively high as compared with that of E. coli Fur to the iucA promoter (5 nM; Ref. 28) and the sodA promoter (10 -20 nM; Ref. 29).…”
Section: Determination Of the Transcription Start Site For Fatdcba Mrmentioning
confidence: 96%
“…Based on in vitro data it has been suggested that the E. coli Fur protein is active as a dimer or as a multimer (17,18,28) that binds to its 19-bp dyad symmetrical operator sequence, so called Fur consensus sequence or iron box (19, 28; Fig. 7) in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, Fur seems to polymerize around the DNA of the aerobactin promoter with a precise directionality but unclear stoichiometry. Furthermore, one study by Wee et al (1988) suggested that Fur could form tripartite complexes with the target DNA sequences and the RNA polymerase (RNAP).…”
Section: Introductionmentioning
confidence: 99%